Efficacy and safety of immune checkpoint inhibitors plus recombinant human endostatin therapy as second-line treatment in advanced non-small-cell lung cancer with negative driver gene: a pilot study - Yang, Bo; Li, Yuzhi; Deng, Jie; Yang, Hui; Sun, Xiang (Frontiers in Oncology, 2023)
Background: Immune checkpoint inhibitors (ICIs) have become the standard second-line treatment for advanced non-small cell lung cancer (NSCLC). Recent findings indicating an intertwined regulation of vascular endothelial growth factor (VEGF) signaling and immunosuppression in the tumor microenvironment suggest that the combination of ICIs and angiogenesis inhibitors could have synergistic antitumor activity, along with favorable tolerability. However, ICIs plus anti-angiogenesis therapy has not been widely evaluated. The purpose of this pilot study was to evaluate the efficacy and safety of ICIs plus recombinant human (rh)-endostatin as second-line treatment in advanced NSCLC with negative driver gene. Method: Prospectively evaluated the efficacy and safety of ICIs plus rh-endostain as second-line treatment in advanced NSCLC with negative driver gene. The primary endpoints of the study were progression-free survival (PFS) and overall survival (OS). The secondary endpoints were objective response rate (ORR), disease control rate (ORR), and safety. Results: A total of 34 patients were recruited in this study. 18 patients received ICIs plus anti-angiogenesis therapy (ICIs combination therapy), and 16 patients received ICIs monotherapy. DCR was 88.9% vs 43.8% (P = 0.009). Median PFS (mPFS) was 8.3 months vs. 3.7 months (HR = 0.276, 95% CI 0.125-0.607, P = 0.001). Median OS (mOS) was 18.0 months vs 9.6 months (HR=0.364, 95% CI 0.147-0.902, P=0.009). In multivariate Cox regression analysis, ICI combination therapy prolonged PFS (HR = 0.069, 95% CI 0.019-0.185, P < 0.001) and OS (HR = 0.044, 95% CI 0.011-0.185, P < 0.001). We did not observe a significant difference in the incidence of adverse events (AEs) between the two groups (P > 0.05). Conclusions: Compared with ICIs monotherapy, ICIs combination therapy improves clinical response in patients with advanced NSCLC with negative driver gene, significantly prolongs PFS and OS, and does not significantly difference the incidence of AEs.